2024
DOI: 10.1021/acsomega.3c10522
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine as an Eco-Friendly Anticorrosion Inhibitor for Mild Steel in Various Acidic Solutions: Electrochemical, Adsorption, Surface Analysis, and Quantum Chemical Calculations

Hanaa. M. Elabbasy,
Arafat Toghan,
Hend. S. Gadow

Abstract: The corrosion of iron in acidic environments has a negative impact on global industry. Herewith, the inhibitory effect of cysteine (Cys.) on mild steel (MSL) corrosion in different acidic solutions (1 M HCl, 1 M H 2 SO 4 , and 1 M H 3 PO 4 ) was investigated through weight loss, potentiodynamic polarization (PDP), electrochemical impedance spectroscopy, scanning electron microscopy (SEM), and theoretical calculations. The measurement results indicated that the adsorption of Cys. molecules on the metal surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Toghan et al discussed the relationship between corrosion potential and zero-charge potential (ZCP) to further explore the adsorption mechanism of corrosion inhibitors. , It has been reported that the ZCP of iron in a HCl solution is equal to −530 mV versus SCE . Clearly, in this study, the corrosion potential is more positive than the ZCP ( E coor – Eq > 0), indicating that the electrode surface is positively charged.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Toghan et al discussed the relationship between corrosion potential and zero-charge potential (ZCP) to further explore the adsorption mechanism of corrosion inhibitors. , It has been reported that the ZCP of iron in a HCl solution is equal to −530 mV versus SCE . Clearly, in this study, the corrosion potential is more positive than the ZCP ( E coor – Eq > 0), indicating that the electrode surface is positively charged.…”
Section: Resultsmentioning
confidence: 59%
“…In the presence of the inhibitor within the corrosive medium, it competes with H + , H 2 O, and C1 – for adsorption sites and establishes the protective barrier, thereby impeding both mass and charge transfer processes and effectively retarding metal corrosion. , …”
Section: Resultsmentioning
confidence: 99%